1993
DOI: 10.1254/jjp.63.9
|View full text |Cite
|
Sign up to set email alerts
|

Thrombolytic Activity of a Novel Modified Tissue-Type Plasminogen Activator, YM866, in a Canine Model of Coronary Artery Thrombosis

Abstract: ABSTRACT-The thrombolytic activity of a novel modified t-PA, YM866, was compared with that of a recombinant t-PA in a canine model of copper coil-induced coronary thrombosis. The coronary thrombus was allowed to age for 1, 3 or 6 hr before either drug was administered. YM866 was administered by i.v. bolus injection, while t-PA was given by the same method, as well as by 60-min i.v. infusion. YM866 show ed thrombolytic activity 2 to 4 times as potent as that of t-PA when administered by bolus injection, the dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
(19 reference statements)
2
12
1
Order By: Relevance
“…However, the thoracic surgery in both these models is complicated, and the treated animal is susceptible to infection after operation, increasing the chance of death. It is possible that the canine models using either copperinduced thrombi [12][13][14] or thrombi by open-chest injection of a thrombin and autogenous blood mixture 1,2 could be used. However, they are primarily used as an acute preparation in which thrombi are induced and then reperfused with thrombolytic agents following an appropriate aging period.…”
Section: Discussionmentioning
confidence: 99%
“…However, the thoracic surgery in both these models is complicated, and the treated animal is susceptible to infection after operation, increasing the chance of death. It is possible that the canine models using either copperinduced thrombi [12][13][14] or thrombi by open-chest injection of a thrombin and autogenous blood mixture 1,2 could be used. However, they are primarily used as an acute preparation in which thrombi are induced and then reperfused with thrombolytic agents following an appropriate aging period.…”
Section: Discussionmentioning
confidence: 99%
“…injection, the reperfusion rate with YM866 was 4 times higher than that with t-PA. By multi ple injection, reperfusion with YM866 was comparable to that with t-PA. We previously reported that the intra venous doses of the agents producing a 100% reperfu sion rate in the same thrombus model were 0.2 mg/kg of YM866, 0.8 mg/kg of t-PA by bolus injection, and 0.3 mg/kg of t-PA by infusion (7). Both agents were twice as potent when given by single i.c.…”
Section: Discussionmentioning
confidence: 91%
“…In the previous study, the residual plasma YM866 and t-PA antigen at 10 min after i.v. bolus injection was 61 % and 20% of the peak levels, respectively (7). Therefore in this study, we ad ministered both agents by a single injection (10 min) or multiple injection (4 x 10 min).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…107 Its half-life is about 30-47 min and is dose-dependent. Its in vitro fibrin affinity is more pronounced and the specific activity in vitro is the same as of t-PA. 23 An intravenous bolus injection of YM866 administered in a canine model of coronary thrombosis exerted a superior thrombolytic effect than t-PA without systemic activation of fibrinolysis in comparison with t-PA. 108 A clinical trial conducted in Japan comparing palmiteplase with t-PA showed that palmiteplase had TIMI-3 flow rates of 25% at 30 min (16% for t-PA) and 50% after 60 min (48% for t-PA), with similar thrombolytic effects. 23 (vii) Amediplase (CGP 42935, K2tu-PA, MEN 9036) It is a hybrid plasminogen activator composed of the kringle 2 domain of t-PA (1-3C 176-275) and the catalytic protease domain of scu-PA (159-411).…”
Section: (Iv) Monteplase (E6010)mentioning
confidence: 99%